Mathematical Literacy Ability Viewed by Students’ Mathematical Habits of Mind Using Quick on the Draw Model With SPUR Approach - Jerau, Emiliana Elsa; Wardono, Wardono; Dwidayati, Nur Karomah (Universitas Negeri Semarang, 2021)
This study aims was describing students' mathematical literacy abilities based on mathematical habits of mind after being given Quick on the Draw learning with the SPUR approach. This research was a qualitative research. Subject of the research were students of class VII SMP Negeri 5 Borong.The results of the study show that (1) Quick on the Draw model with quality SPUR approach in improving students' mathematical literacy skills (2) Students with high mathematical habits of mind had excellent mathematical literacy skills, namely students were very capable of mastering the components of communication, mathematics, reasoning and argument, as well as formulating and solving problems. Students with mathematical habits of mind were showing good mathematical literacy skills. Students were able to master the components of communication, mathematics, and formulate and solve problems. Meanwhile, those that had not been mastering well are representation, reasoning and arguments, and the use of symbols, formal language, techniques, and operations. Students with low mathematical habits of mind show that literacy skills were still not good. Students only master the communication component well enough. Meanwhile, the other components had not been mastering properly.